2023
DOI: 10.1186/s12903-023-03149-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer knowledge, attitudes, and practices among senior dental students in Yemen: a multi-institution study

Anas Shamala,
Esam Halboub,
Sadeq Ali Al-Maweri
et al.

Abstract: Background The “Knowledge, attitude, and practice (KAP)” approach is crucial in health system. Appreciating the current KAP status will reveal the extent of the efficiency of applied health strategies, and subsequently help to determine the appropriate health policy to be employed for improving the health indicators of a given disease/condition, including Oral Cancer (OC). This large-scale cross-sectional study aimed to assess knowledge, attitude, and practice on OC among senior dental students… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This particular condition has also been addressed in the study conducted by Shamala et al , (2023) where significant gaps in knowledge, attitude, and practice were reported among dental students in relation to the management of oral cancer, where gaps were attributed to the limited clinical exposure to the disease. [ 17 ] Furthermore, our analysis indicated that various sociodemographic factors, including gender, clinical interest, and physical proximity to the geriatric population, did not significantly influence the knowledge of dental students regarding xerostomia and AC.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This particular condition has also been addressed in the study conducted by Shamala et al , (2023) where significant gaps in knowledge, attitude, and practice were reported among dental students in relation to the management of oral cancer, where gaps were attributed to the limited clinical exposure to the disease. [ 17 ] Furthermore, our analysis indicated that various sociodemographic factors, including gender, clinical interest, and physical proximity to the geriatric population, did not significantly influence the knowledge of dental students regarding xerostomia and AC.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies by Tahani et al [ 19 20 ] have highlighted the inadequacy of geriatric dentistry modules in the dental education system of Iran. [ 22 ] In contrast, Kossioni et al [ 17 20 ] reported that many European countries have successfully introduced focused modules on geriatric dentistry, with 86.2% of schools incorporating such modules. [ 23 ] However, there is limited information regarding the introduction and standardization of geriatric dentistry modules in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of confidence may be attributed to a lack of clinical exposure to patients with oral cancer cases in comparison to routine dental problems. It is a well-recognized gap in dental education that can be bridged through structured clinical exposure to specialist settings in oral and maxillofacial surgery, use of case-based discussions and clinical problem-solving sessions [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dentists’ awareness of OC risk factors and lifestyle modifications can help to prevent OC and improve survival rates among patients [ 18 ]. Many studies worldwide have investigated dentists’ knowledge, awareness, and practices for preventing and early diagnosing OC [ 13 , 15 41 ]; however, no study has compared the knowledge levels of dentists and senior dental students regarding OC.…”
Section: Discussionmentioning
confidence: 99%